Pengembangan Pariwisata Pasar Terapung Kota Banjarmasin - Herry Pradana (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2020)
The importance of developing the region’s leading sectors based on regional uniqueness and competitiveness will accelerate regional economic growth. Tourism development is expected to be one of the drivers of economic growth, as can be seen from its contribution to economic growth, employment opportunities, income generation, and equitable development. The city of Banjarmasin is known as a city of trade and services in South Kalimantan, establishing river tourism as one of its leading sectors to support the economy. This study aims to formulate strategies for developing floating market tourism at the City of Banjarmasin. The development of the Floating Market tourism as a main component of the regional innovation system aims to revive the Floating Market with a modern tourism approach based on innovation and cultural reengineering. This research uses qualitative research with an explorative descriptive approach and analyzed using the SWOT method. The development of river-based tourism with the Floating Market as its main icon will have a major impact on their economy if it is managed and developed seriously and comprehensively. Based on the results of the SWOT analysis, the development of the floating market will be focused on the development of the river tourism ecosystem in the form of river cruises and the development of transit points along the river for the craft and culinary centers. Abstrak Pentingnya mengembangkan sektor-sektor unggulan berbasis keunikan/kekhasan daerah akan mempercepat pertumbuhan ekonomi regional. Pembangunan pariwisata sebagai sektor unggulan diharapkan dapat menjadi salah satu motor penggerak pertumbuhan ekonomi, hal ini dapat dilihat dari kontribusi pariwisata pada pertumbuhan ekonomi dan penciptaan peluang kerja, peningkatan pendapatan masyarakat dan pemerataan pembangunan. Kota Banjarmasin sebagai kota perdagangan dan jasa telah menetapkan pariwisata sungai sebagai salah sektor unggulannya. Penelitian ini bertujuan untuk merumuskan strategi pengembangan pariwisata Pasar Terapung di Kota Banjarmasin. Pengembangan pariwisata Pasar Terapung merupakan komponen utama Sistim Inovasi Daerah (SIDa) Kota Banjarmasin yang bertujuan untuk menghidupkan kembali geliat Pasar Terapung dengan pendekatan pariwisata modern berbasis inovasi dan rekayasa budaya. Penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif eksploratif dan dianalisis menggunakan metode SWOT. Pengembangan pariwisata berbasis sungai dengan Pasar Terapung sebagai icon utama daerah akan memberikan dampak yang besar bagi Kota Banjarmasin apabila dikelola dan dikembangkan secara serius dan komprehensif. Berdasarkan hasil analisis SWOT, pengembangan pasar terapung difokuskan pada pengembangan ekosistem pariwisata sungai berupa susur sungai dan pengembangan titik persinggahan disepanjang sungai berupa sentra kerajinan dan sentra kuliner.